Heterozygous variants in transmembrane channel-like 1 gene cause autosomal recessive nonsyndromic hearing loss: TMC1 variants in ARNSHL - Zhang, Lan; Zhu, Qingwen; Wu, Yanzhao; Shi, Ping (Cellular and Molecular Biology, 2024)
Autosomal recessive non-syndromic hearing loss (ARNSHL) can cause severe or very severe pre-speech hearing loss. Transmembrane channel-like 1 (TMC1) gene is the sixth deafness gene discovered, but the precise extent of its protein structure and function is unknown. First, history collection, audiology examination and imaging examination were performed on the proband and his family members. Peripheral blood of proband and family members was collected, genomic DNA was extracted, exon high-throughput sequencing technology was used to detect the deafness gene mutation of the proband, and Sanger sequencing was performed to verify the TMC1 gene of the proband's parents. The proband was born with hearing impairment, normal tympanic function, inability to induce acoustic reflex in both ears (acoustic reflex threshold is 100 dBHL), and severe sensorineural deafness. One of his sisters has severe sensorineural hearing loss, and neither his parents nor his other sister is hearing impaired. High-throughput sequencing of the proband identified mutations at c.741+3_741+6delAAGT (splicing) and c.884C>T (p.A295V) of the TMC1 gene, two of which were heterozygous mutations. Sanger sequencing confirmed that the c.884C > T mutation was inherited from the mother, while the c.741+3_741+6delAAGT mutation was derived from the father. Prediction of amino acid function suggested that both mutations were pathogenic mutations. In conclusion, we found a new pathogenic complex heterozygous mutation of the TMC1 gene, which enriched the mutation spectrum of the TMC1 gene and provided a basis for genetic counseling and prenatal diagnosis of ARNSHL.